The relevance of editorial issues and the position of the editor in the creation of media content (Eurasian Journal of Media and Communications, 2022)
The relevance of editing issues and the position of the editor in the creation of media content were studied through practical examples and surveys. The results of our research have shown that every aspect is important for the proper organization of the newspaper's media content. In order to choose the right topic, to match the title and the topic, to choose an image that matches the content of the text, to eliminate spelling and stylistic errors, to pay attention to page design, to ensure the diversity of articles, we looked at attracting foreign authors